Functional Mitral and Tricuspid Regurgitation Pathophysiology, Assessment and Treatment - Chan, Kok Meng John.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book covers in detail all aspects of functional mitral and tricuspid regurgitation, from its pathophysiology and natural history, to its assessment, medical and surgical treatment, and long term results. Functional Mitral and Tricuspid Regurgitation encompasses information and knowledge from a diverse background including cardiology, cardiac surgery and basic science. This is necessary for a full understanding of the subject in order to optimally manage patients with this condition.
The normal mitral valve and mitral regurgitation -- Pathophysiology of ischemic mitral regurgitation -- Assessment of ischemic mitral regurgitation -- Treatment of ischemic mitral regurgitation -- B-type natriuretic peptide in ischemic mitral regurgitation -- Randomized trials in ischemic mitral regurgitation -- Predictors of outcome -- What still needs to be done.
Keywords: Medicine; Cardiac imaging; Cardiology; Cardiac surgery; Medicine & Public Health; Cardiology; Cardiac surgery; Cardiac imaging